Diário de aula: registros do (re)pensar docente a respeito da avaliação de ensino-aprendizagem no contexto de privação de liberdade - Soares, Carla Poennia Gadelha (2018)
The general objective of this thesis is to investigate the way in which teachers and incarcerated students use the writing of classroom journals to narrate their experiences regarding the evaluation of teaching-learning. Specifically, the objectives are: i) to describe the meanings attributed by the students to the assessment of teaching-learning through the writing of classroom journals; ii) to identify the teaching dilemmas about the evaluation of learning which is narrated in the classroom journals; and iii) to present the changes in teachers' understanding related to the evaluation of teaching-learning during their experience with the pedagogical use of classroom journals. These objectives, when achieved, support the thesis that the writing of classroom journals favors the systematization of evaluation practices and contributes to the achievement of an evaluation which is committed to the quality of both student and teacher development, since the journal itself is already a reflective process on teaching and learning. That is, journaling has the potential to offer benefits such as teachers understanding how and when they evaluate, what they value most, what students feel and think about how they evaluate; thus, journaling can promote resizing of educational planning with respect to the evaluation of teaching-learning. This study is theoretically based on the works of Porlán (1987) and Zabalza (2004) on the reflective use of classroom journals to improve teaching practice and, consequently, student learning. Methodologically, qualitative and collaborative research was conducted in the form of a case study. The research was conducted in classrooms at EEFM Aloísio Leo Arlindo Lorscheider. The sample consisted of 72 subjects, 62 of whom were incarcerated students and 10 teachers. Semi-structured interviews, document analysis and reflective sessions were used as research tools. The results indicate that classroom journals also served as evaluative records for the teachers and not only as reflective records about their own practices, since they were often used to note observations about the students and their learning. By its reflective and cathartic character, journaling has provided a means for teachers and students to express not only elements of their educational universe, but also of their life histories. All of the teachers participating in this study revealed that their conceptions of evaluating teaching-learning changed during the pedagogical use of classroom journals.